Analysis of Passenger Transportation Demand: Case Study of the Customs House, the Thai-Laos Friendship Bridge, Nong Khai Province - Nonthapot, Sakkarin (Journal of Social and Development Sciences, 2014)
This study analyses the factors influencing passenger transportation demand at the Thai-Laos Friendship Bridge in Nong Khai Province, Thailand. Secondary data was collected from July 2007 to June 2010. The passenger transportation demand model estimation via a unit root test prior to the ordinary least square (OLS) technique found that the passenger number has a long-term, positive equilibrium relationship with the price. On the other hand, gross domestic product (GDP) and the frequency of services provided, have a negative relationship with the exchange rate. The empirical results of a short term analysis based on the error correction mechanism (ECM) estimation revealed that the adjustment speed that affects the number of passengers deviates from the equilibrium point to the long-term equilibrium point by 46.3 percent in each time period. Proposed policy recommendations are as follows: entrepreneurs should increase the frequency and number of services; wider variety of vehicles should be provided; each vehicle should run at full capacity; overall improvement in speed, safety and efficiency of the services is also necessary.